Problematika Internal Nelayan Tradisional Carocok Kecamatan Koto XI Tarusan: Studi Faktor-faktor Sosial Budaya Penyebab Kemiskinan - Hoktaviandri Hoktaviandri (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2018)
This paper describes the problem of fishermen's family in maintaining a family economy carried out by a fisher housewife in Carocok Subdistrict Koto XI Tarusan to survive socio-economic pressures. Poor fishermen in Carocok Subdistrict Koto XI Tarusan is rooted in complex factors, namely natural and non-natural factors. The struggle of poor fisher housewives in survival is not only influenced by their environmental work ethic, but also influenced by the progress of Carocok Koto XI Tarusan Subdistrict which further increases the level of difficulty in maintaining their family's economy, even infectious diseases that are not detected by the government. The socio-economic difficulties they face, instead make it smarter to take alternatives with the social resources around them to survive.